2018
DOI: 10.1097/id.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

Implant-Supported Fixed Partial Prostheses With Different Prosthetic Materials

Abstract: ZRPMMA had the lowest stress values in the framework, with increased stress values in the implants and bone tissue. Framework and veneering materials may influence stress values under different loading conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…In numbers, the results were very similar, demonstrating again that the variation in crown material does not have a significant impact on the risk of fracture of the structure, since, as in the works of Gungor & Ylmaz (2016), Kaleli (2017) and Arinc (2018 ), the values found did not exceed the flow limits of the materials. This suggests a long clinical shelf life under the observed conditions (27,28,29).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In numbers, the results were very similar, demonstrating again that the variation in crown material does not have a significant impact on the risk of fracture of the structure, since, as in the works of Gungor & Ylmaz (2016), Kaleli (2017) and Arinc (2018 ), the values found did not exceed the flow limits of the materials. This suggests a long clinical shelf life under the observed conditions (27,28,29).…”
Section: Discussionsupporting
confidence: 63%
“…There are four main factors that can affect the results in predicting the biomechanical behavior of stresses, such as the geometric detail of the object to be modeled, number of nodes and elements, types and properties of selected elements and boundary conditions. To carry out the analyzes in this work, as used by Gil (2017) and Arinc (2018), all materials used in the research were also considered homogeneous and isotropic, that is, all mechanical properties were considered the same, in all directions at the same point of the structural element (30,29).…”
mentioning
confidence: 99%
“…Although low‐elasticity modulus materials had a shock absorption effect, 22 the PEEK and CFR‐PEEK frameworks were not as effective as pure titanium and zirconia in improving the stress distribution, especially implant stress, in this study. Several previous studies reported that the shock absorption effect of polymeric materials was low 16,22 and accompanied by a low stress value in the framework and a high stress value in bone 22,43 . This finding indicates that polymeric materials pose a significant risk of bone resorption.…”
Section: Discussionmentioning
confidence: 82%
“…Several previous studies reported that the shock absorption effect of polymeric materials was low 16,22 and accompanied by a low stress value in the framework and a high stress value in bone. 22,43 This finding indicates that polymeric materials pose a significant risk of bone resorption. Some reports also demonstrated that a rigid material could resist more stress than an elastic material, 15,21,44 which is consistent with the present study.…”
Section: Discussionmentioning
confidence: 92%
“…The contact between the different structures was considered "bonded", meaning without sliding. All FPD infrastructures were metal-free with a zirconia infrastructure (modulus of elasticity 269,000 MPa and Poisson's ratio 0.25 -reference by Arinc [16] and Gungor & Yilmaz [17]), with feldspathic ceramic coating (modulus of elasticity 80,000 MPa and Poisson's ratio 0.30 -reference by Arinc [16] and Erkmen et al [18]), and closure of the screw holes with composite resin. The bones were type I, considered to be of good quality.…”
Section: Methodsmentioning
confidence: 99%